Passivum. przeciw antropomorfizmowi = The passive voice. Against Anthropomorphism - Termińska, Kamilla (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The preliminary hypotheses of the article are the following: the assumption con- cerning semantization of morphological categories and the thesis that the semantics in ques- tion consists of hardened fossils of ontological theories. Examining the meanings inherently present in the Polish passive voice, but foreign to Semitic languages like classical Hebrew, we encounter - unauthorized in the light of the existing analyses - the myth of anthropocentrism.
Keywords: relatywizm kulturowy; orientalizm; bierno-refleksywne koniugacje hebrajszczyzny biblijnej; semantyka polskiej strony biernej; mit antropocentryzmu; cultural relativism; orientalism; passive-reflexive conjugations of Biblical Hebrew; semantics of the Polish passive voice; myth of anthropocentrism